Tenofovir-Based Preexposure Prophylaxis for HIV Infection Among African Women. Issue 7 (July 2015) - Marrazzo, Jeanne M.; Ramjee, Gita; Richardson, Barbra A.; Gomez, Kailazarid; Mgodi, Nyaradzo; Nair, Gonasagrie; Palanee, Thesla; Nakabiito, Clemensia; van der Straten, Ariane; Noguchi, Lisa; Hendrix, Craig W.; Dai, James Y.; et al.
Abstract : ABSTRACT: Reproductive-age African women and others at high risk of acquiring human immunodeficiency virus type 1 (HIV-1) infection need effective interventions to prevent acquisition of this virus. Previous studies have demonstrated that daily oral pre-exposure prophylaxis with tenofovir disoproxil fumarate (TDF) alone or TDF combined with emtricitabine (FTC) (TDF-FTC) reduces the risk of HIV transmission by at least 50% in men who have sex with men, heterosexuals, and injection-drug users (with greater effectiveness in subjects with high adherence to the regimen). However, daily tenofovir (TFV)–based regimens were found to be ineffective in preventing HIV-1 acquisition among women in the Preexposure Prophylaxis Trial for HIV Prevention among African Women (FEM-PrEP) when adherence to the regimen was less than 40%. The Vaginal and Oral Interventions to Control the Epidemic (VOICE) trial was a randomized, placebo-controlled trial that assessed the effectiveness of daily treatment with oral TDF, oral TDF-FTC, or 1% TFV vaginal gel in preventing sexually acquired HIV-1 infection in women in South Africa, Uganda, and Zimbabwe. Adverse effects of the regimens were also assessed. Monthly HIV tests and quarterly blood testing were performed. From September 2009 through June 2011, 12, 320 women were screened at 15 sites in South Africa, Uganda, and Zimbabwe. Of these, 5029 were enrolled in the study and randomized. Retention in the trial was excellent; 91% of women completed follow-up visits. The primary effectiveness end point, HIV-1 infection, was identified by seroconversion and assessed in a modified intention-to-treat population. There were 312 HIV-1 infections among study participants; the incidence of infection was 5.7 per 100 person-years. None of the TFV-based regimens were effective in reducing HIV-1 transmission: effectiveness was −49.0% for TDF alone (hazard ratio [HR] for infection, 1.49; 95% confidence interval [CI], 0.97–2.29), −4.4% for TDF-FTC (HR, 1.04; 95% CI, 0.73–1.49), and 14.5% for TFV gel (HR, 0.85; 95% CI, 0.61–1.21). Adherence appeared to be high (86%) based on women's returns of empty pill boxes and gel applicators. However, measurable drug plasma levels in random samples were only 30% for TDF, 29% for TDF-FTC, and 25% for TFV gel. Independent predictors of adherence included being married, being older than 25 years, and being multiparous. There were elevated serum creatinine levels more frequently among participants who received oral TDF-FTC compared with oral placebo (1.3% vs 0.2%, P = 0.004). No significant differences were noted in the frequencies of other adverse events. Consistent with the findings of other studies, these data show that TDF-based regimens proven to prevent HIV infection are ineffective when adherence is poor.